An Assessment of Entrepreneurial Affinity in Bangladesh: A Comparative Analysis between Small Live Entrepreneurs and Potential Entrepreneurs of University Level Students (Journal of Business and Technology (Dhaka), 2016)
This is an empirical and quantitative study conducted on small scale live entrepreneurs and potential entrepreneurs of university level students of Bangladesh. The main purpose of this study is to identify and examine the factors influencing decision of becoming an entrepreneur. For fulfilling the study purpose, by using simple random sampling technique a total of 600 questionnaires were administered; 300 were distributed to the students who were interested to become entrepreneurs and 300 questionnaires were also distributed to small scale live entrepreneurs who formed their business during the last two years and more. Data were analyzed according to objectivity. The results indicated that need for achievement is highly influential factor in picking up decision of becoming an entrepreneur of potential entrepreneurs of university level students and family business background is the main influential factor in taking decision of becoming an entrepreneur of the small scale live entrepreneurs. Parallel factors, e.g., locus of control, risk taking propensity and proactive personality also acted as the influential factors of creating entrepreneurial affinity in both of them.Journal of Business and Technology (Dhaka) Vol.10(1) 2015; 1-20